Carvacrol alters soluble factors in HCT-116 and HT-29 cell lines - PAKDEMİRLİ, Ahu (Turk J Med Sci, 2020)
BACKGROUND/AIM: Natural products are popular insights for researchers to investigate promising anti-cancer agents since some of these substances have lesser adverse effects restricting the treatment than traditional chemotherapeutic agents. A well-known monoterpene Carvacrol, widely consumed in Mediterranean cuisine and lower risks of cancer, has efficient anticancer effects. However, the mechanism of action is yet to be discovered. MATERIALS AND METHODS: The investigation aims to illuminate a new perceptive in the role of this substance on colorectal cancer treatment, by the means of differences in a well-defined range of soluble factors. Carvacrol effect on both HT-29 and HCT-116 cell lines was evaluated on proliferation and the IC50 values were calculated by the RTCA xCELLigence device. Then MAGPIX assay was performed to obtain the changes in soluble factors of the cell lines. RESULTS: The Multiplexing assay suggests some of these factors were altered in favor of surviving and proliferation in aggressive cell line HCT-116 whereas they were altered against these characters in HT-29, were correlated with the increased IC50 concentration of HCT-116 in carvacrol treatment. CONCLUSION: The current study indicates that differences in the levels of these soluble factors could modulate the anticancer effect related to carvacrol.